Wordsworth as Critic - Owen, W. J. B. (Warwick Jack Burgoyne) (Book collections on Project MUSE., 1969)
This book is the first full-scale account of the growth of Wordsworth's thinking about the theory of poetry. It draws mainly on his formal critical essays but also on unpublished material and personal statements about poetics and the growth and constitution of the poet's mind in The Prelude, in other verse, and in letters.